One stop MUET portal / Zetty Harisha Harun... [et al.] - Harun, Etty Harniza; Harun, Robekhah; Mohammed, Syakirah; Ibrahim, Syazliyati; Hasan, Asrol (Universiti Teknologi MARA, Kedah, 2013)
ONE STOP MUET PORTAL is designed to accommodate UiTM students’ need to score higher bands in the examination. It will also be used to help and also familiarize the students on the rules and regulations of the MUET papers and the syllabus specifications and skills outlined in the syllabus. Links to helpful websites will also be made available for the students in the portal. In addition, sample question papers will also be available for the students to try. Last but not least, the ability to interact directly with the students will be the main attraction for the students to use the portal as an early preparation for the examination.